2019
DOI: 10.1002/cam4.2595
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in timeliness of care and outcomes for anal cancer patients

Abstract: Background Socioeconomic status (SES) is associated with diagnostic and treatment delays and survival in multiple cancers, but less data exist for anal squamous cell carcinoma (ASCC). This study investigated the association between SES and outcomes for patients undergoing definitive chemoradiation therapy for ASCC. Methods One hundred and eleven patients diagnosed with nonmetastatic ASCC between 2005 and 2018 were retrospectively reviewed. Socioeconomic predictor variables included primary payer, race, income,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
2
10
1
Order By: Relevance
“…Nevertheless, Lin et al (2018), using the same database for patients diagnosed from 2004-2013, agreed that patients living in geographical areas with low median household income had poorer survival; however, their data suggested that male patients (rather than female patients), African American patients and older age were associated with worse survival [9]. A further American study looking at the relationship of SES and end outcomes in patients diagnosed with ASCC suggested that low SES was not associated with stage but with a reduction in relapse free and overall survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Lin et al (2018), using the same database for patients diagnosed from 2004-2013, agreed that patients living in geographical areas with low median household income had poorer survival; however, their data suggested that male patients (rather than female patients), African American patients and older age were associated with worse survival [9]. A further American study looking at the relationship of SES and end outcomes in patients diagnosed with ASCC suggested that low SES was not associated with stage but with a reduction in relapse free and overall survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…[15,22,23] Social support is crucial in cancer survivors due to the enormous psychosocial burden of anal cancer. [22,23] Other studies have revealed that single partnership status is associated with delayed treatment, [24] implying that a lack of partner may be an independent risk factor for patients with anal cancer. Therefore, more attention should be given to elderly patients without a partner.…”
Section: Discussionmentioning
confidence: 99%
“…Two published analyses of patients with anal cancer suggest that Black patients have longer delays to initiation of chemoradiation and also have inferior survival. 15,16 Similarly, Hispanic patients with anal squamous cell carcinoma have been found to have longer delays in start of chemoradiation than NHW patients. 18 NHB and Hispanic women with cervical cancer have longer treatment delays than NHW patients, with IMRT utilization correlated with longer delays.…”
Section: Discussionmentioning
confidence: 99%
“…Limited published data suggest that sociodemographic factors including race, ethnicity, and insurance coverage may contribute to delays in IIT of RT. [15][16][17][18][19][20] As IMRT utilization has significantly increased over the past decade, a contemporary examination of the burden of treatment delays and disparities in timely initiation of definitive IMRT is needed. 21 We hypothesize that delays in initiation of therapy associated with the use of advanced radiotherapy modalities disproportionately affect minoritized patients.…”
Section: Introductionmentioning
confidence: 99%